1991
DOI: 10.1002/art.1780340110
|View full text |Cite
|
Sign up to set email alerts
|

Induction of arthritis in rats by aqueous suspensions of mycobacteria without the use of oil

Abstract: We report for the first time the induction of arthritis by an aqueous, rather than an oil, suspension of killed tubercle bacilli. This was accomplished in the highly susceptible dark Agouti strain of rats, by intraperitoneal injection during the healing phase of chemically induced peritonitis. The same procedure (injection after the induction of peritonitis) augmented the incidence of arthritis produced by bovine type I1 collagen and Freund's complete adjuvant. Enhanced delivery of antigen from the peritoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…AIA develops in susceptible rat strains after the injection of FCA (1)(2)(3)(4)(5)(6)(7)(8)(9). The first step in the development of AIA is the production of an immune response to FCA.…”
Section: Discussionmentioning
confidence: 99%
“…AIA develops in susceptible rat strains after the injection of FCA (1)(2)(3)(4)(5)(6)(7)(8)(9). The first step in the development of AIA is the production of an immune response to FCA.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between DA rats and Lewis rats have been recently emphasized by the different characteristics of arthritis induced with rat collagen in these 2 strains (5) and the differences in susceptibility of these animals to aqueous suspensions of adjuvant (6). Other studies have also emphasized the varied arthritogenic responses among different rat strains (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Increased absorption of antigen into the lymph nodes is likely to increase the immune response. Recently, it has been found that absorption of antigens and other materials from the peritoneal cavity of rats is increased during the healing (postinflammatory) phase of a chemical peritonitis [1][2][3][4], Subsequent enhancement of the immune response has been found in studies of hemagglutinating antibodies [5] and several forms of cellmediated immunity: graft-vs.-host disease and hostvs.-graft response [2], experimental allergic encepha lomyelitis and adrenalitis [2,[6][7][8][9][10], and adjuvant arthritis [11]. In the present work, enhancement of sys temic anaphylaxis has been produced by sensitizing or challenging rats in the postinflammatory state.…”
Section: Introductionmentioning
confidence: 99%